2005
DOI: 10.1007/s10488-004-1662-3
|View full text |Cite
|
Sign up to set email alerts
|

Overview Of Publicly Funded Managed Behavioral Health Care

Abstract: Using MEDLINE and other Internet sources, the authors perform a systematic review of published literature. A total of 109 articles and reports are identified and reviewed that address the development, implementation, outcomes, and trends related to Managed behavioral health care (MBHC). MBHC remains a work in progress. States have implemented their MBHC programs in a number of ways, making interstate comparisons challenging. While managed behavioral health care can lower costs and increase access, ongoing conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…National rates and general patterns of psychotherapy use have remained remarkably consistent despite important changes in the private and public fi nancing of mental health care (15,16). Beginning on January 1, 1998, the federal Mental Health Parity Act prohibited employerbased group health plans with more than 50 workers from having different annual lifetime benefi t limits for mental health and general medical illnesses (17).…”
Section: Psychotherapy Expendituresmentioning
confidence: 99%
“…National rates and general patterns of psychotherapy use have remained remarkably consistent despite important changes in the private and public fi nancing of mental health care (15,16). Beginning on January 1, 1998, the federal Mental Health Parity Act prohibited employerbased group health plans with more than 50 workers from having different annual lifetime benefi t limits for mental health and general medical illnesses (17).…”
Section: Psychotherapy Expendituresmentioning
confidence: 99%
“…This is especially important given that prescription drug spending has been growing during a period when inpatient and outpatient mental health care has not been growing. Last, some evidence indicates that the impact of a carve-out may change over time as it is implemented and matures (16), so results at a given point in time may not hold true over the long term.…”
Section: Performancementioning
confidence: 99%
“…4 Frank & Lave's 2003 review of studies (25) shows cost savings in Colorado, Massachusetts, North Carolina, and Utah ranging from 17% to 33%. Some more recent reviews note that some states with immediate cost decreases have found that the declines may have represented one-time savings because these levels were difficult to sustain over time (6,16,59 (25) note that the similarity of cost savings in studies that examine only services included in the carve-out and those that examine all behavioral health services (regardless of contractual responsibility) indicates minimal cost shifting to primary care providers. Similarly, Cuffel et al (18) explicitly compare costs for general medical care before and after a carve-out and find lower overall health care spending after the carve-out.…”
Section: Performancementioning
confidence: 99%
“…1). Service providers receive a total budget for all forms of inpatient and hospital-based outpatient care (capitation principle [14, 15]). This budget must cover all expenses, yet, leaving sufficient space for adapting treatments to the needs of a region or patient.
Fig.
…”
Section: Introductionmentioning
confidence: 99%